1316. Gathering Trauma Narratives: A Qualitative Study on the Impact of Traumas on People Living with HIV (PLWH) - Pierson, Doris (Open Forum Infect Dis, 2019)
BACKGROUND: Trauma—emotional, physical, and psychological—is common and associated with increased risk behaviors, low rates of care engagement and viral suppression, and overall poor health outcomes for people living with HIV (PLWH). In the United States, there are limited data on how trauma affects reproductive health beliefs for PLWH and even less data on HIV providers’ understanding and consideration of these experiences in their approach to patients. METHODS: Fifteen semi-structured interviews were conducted with PLWH and nine semi-structured interviews were conducted with HIV care and service providers at an academic medical center in the Southeastern United States. Transcripts were analyzed using thematic analysis. Each transcript was coded by two investigators and discussed to ensure consensus. RESULTS: Participants’ narratives described diverse traumas, including sexual abuse (n = 6), the loss of a loved one (n = 8), and personal illness (n = 7). Types of trauma shared with providers included physical, sexual, illness, loss, and psychological. For patients, trauma was both a motivation for having children and a reason to stop having children. Providers perceived a variety of effects of trauma on both sexual behaviors and reproductive intentions. Reproductive counseling by HIV care providers (n = 5) focused on maintaining a healthy pregnancy and less on reproductive intentions prior to pregnancy. Reproductive discussions with pregnant female patients typically centered on reducing the risk of transmission in utero (including the importance of medication adherence to maintain viral suppression), what will happen during delivery, and breastfeeding risks. Reproductive discussions with males typically centered on preventing infection or re-infection of the mother. CONCLUSION: PLWH interpret their trauma experiences differently, particularly when considering reproduction. Providers may not incorporate this information in counseling around reproductive health, highlighting the need fora trauma-informed healthcare practice that promotes awareness, education on the effect of past traumas on health, and access to appropriate resources. DISCLOSURES: All authors: No reported disclosures.